Characterization of fresh juice from Basmati (Oryza sativa) straw. - Roldan, Ritzie Anne S.
Juice from fresh fruits or vegetables is known for their nutraceutical properties, particularly antioxidant activities. This study used Basmati rice straw for fresh juice making. Basmati rice was grown in a vermicompost mixture at the UPV Reforstation Project and Nursery to obtain the 15-day old plant. The rice straw was blanched for 10 minutes at 1000C before processing juice. The three juice formulations varied in weight (fresh basis) of the straw such as: 50g (Formulations1), 75g (Formulation 2), and 100g (Formulation 3) in 500 mL mineral water. All formulations received lemon juice and brown sugar in uniform amounts. The most preferred formulation was the blanched frsh Basmati rice straw with 75g weight per 500 mL volume of water. Friedman?s ANOVA at 95% confidence level indicated that the three formulations significantly differ from each other based on the flavor. Multiple comparison tests showed no significant difference between F1 and F2 and F3 were significantly different in ranking preference in based on flavor. The most preferred formulation was subjected to physico-chemical analysis, radical scavenging activity and sensory test. The blanched fresh Basmati straw juice has vitamin C content of 8.16%, minerals (ash) of 1.00% fiber content of 2.99%. The blanched fresh Basmati rice straw has a mean moisture content of 88.01%. The radical scavenging activity of the juice measured through DPPH method was 74.84% and compared to the standard ascorbic acid with %RSA of 98.15. Although the juice is lower by 21.31% from the standard, its antioxidant activity is considered high. Sensory test assessed the juice as dull green in color, has a sweet taste and slightly detectable rice aroma.